Enhanced vagal modulation and exercise induced ischaemia of the inferoposterior myocardium. Issue 3 (6th June 2005) - Kawasaki, T; Azuma, A; Kuribayashi, T; Taniguchi, T; Asada, S; Kamitani, T; Kawasaki, S; Matsubara, H; Sugihara, H
Abstract : Objective: To determine whether the Bezold-Jarisch reflex or enhancement of vagal nerves, which are preferentially distributed in the inferoposterior myocardium, results from exercise induced ischaemia in this region. Methods: On the basis of exercise myocardial scintigraphy and coronary angiography, 145 patients were classified as follows: group I, 34 patients with inferoposterior ischaemia; group A, 32 with anterior ischaemia; and control, 79 without ischaemia. The relation between ischaemic areas and ECG leads with ST segment changes and vagal modulation assessed by heart rate variability (HRV) (high frequency (HF) component (0.15–0.40 Hz) and coefficient of HF component variance (CCVHF ), which is the square root of HF divided by mean RR interval) were assessed. Results: The rate of ST segment depression in any lead did not differ between group I and group A. HF and CCVHF were similar before exercise but higher in group I than in group A and the control group after exercise (mean (SEM) HF: 94 (17) ms 2, 41 (7) ms 2, and 45 (6) ms 2, respectively, p = 0.021; CCVHF : 1.18 (0.09)%, 0.81 (0.07)%, and 0.89 (0.05)%, p = 0.0053). Furthermore, the percentage change in CCVHF before and after exercise was higher in group I than in group A or controls (mean (SEM) 22 (10)%, −24 (4)%, and −21 (3)%, p < 0.0001). The optimal cut off for diagnosis of inferoposterior ischaemia was −5% with a sensitivity of 74%, specificity 75%, and accuracy 75%. Conclusions: Vagal modulation as assessed by HRV analysis was enhanced in association with exercise induced inferoposterior ischaemia. Exercise ECG testing combined with HRV analysis would increase accuracy in the diagnosis of ischaemic areas in selected patients with angina pectoris.